The Role of the Indonesian Young Entrepreneurs Association in the Development of Young Muslim Entrepreneurs in Ponorogo Regency - Yoga Adi Pratama; Yulia Anggraini (Niqosiya: Journal of Economics and Business Research, 2026)
This study discusses the role of the Indonesian Young Entrepreneurs Association (HIPMI) in developing young Muslim entrepreneurs in Ponorogo Regency. The study is important because young entrepreneurs need support through mentoring, networking, and entrepreneurship development based on Islamic values. This research used a qualitative field study approach. Data were collected through interviews, observations, and documentation with HIPMI administrators and members. Data analysis used the Miles and Huberman model with triangulation techniques. The results show that HIPMI plays facilitative, educational, representative, and technical roles through business networking, entrepreneurship training, mentoring, and cooperation with external parties. HIPMI also strengthens the entrepreneurial ecosystem through training programs and collaboration with HIPMI PT. However, challenges such as limited participation and organizational stigma are still present. In conclusion, HIPMI contributes to improving entrepreneurial skills, business relationships, and the entrepreneurial spirit of young muslim entrepreneurs in Ponorogo Regency.